Energy Efficiency in the Industrial Process of Hair Fiber Depigmentation: Analysis and FEM Simulation. (November 2016) - Carlini, Maurizio; Mennuni, Andrea; Allegrini, Elena; Castellucci, Sonia
Abstract: In this paper the influence of heat transfer in industrial human hair depigmentation is studied together with some suitable solutions for optimizing the industrial process and the efficient energy use. In particular, the analysis was conducted by implementing the current process and the proposed solutions in Comsol Multiphysics. The fiber's damage and the energy loss are mainly due to a non-isothermal uncontrolled process. In order to implement an efficient energy use and to reduce the energy loss we propose a modification of the tank, where the depigmentation occurs, from a rectangular to an octagonal-shape configuration, characterized by the presence of located thermal sources. It will be shown that the depigmentation process realized with the heated octagonal tank structure significantly reduce the energy use. By reducing the thermal stress, arising in an invasive chemical procedure such as depigmentation, we obtain also a significant reduction of the hair-fibers damage.